Ultrasonographic findings in pediatric fractures - Ekşioğlu, Fatih; Altinok, Deniz; Uslu, M Murad; Güdemez, Eftal (The Turkish Journal of Pediatrics, 2003)
The aim of this study was to document and analyze ultrasonographic (US) findings in different types of pediatric fractures. Thirty-nine patients, aged between 1 and 14 years, with a fracture were included in the study. Patients were classified as complete or incomplete fractures. Greenstick fractures, torus fractures and plastic deformations were considered as incomplete fractures. Ultrasonographic findings (subperiosteal hematoma, bending, cortical disruption, and reverberating echo) were analysed for each type of fracture. Subperiosteal hematoma was present in all patients in the study. Bending sign was present in all patients in the incomplete fracture group, but not present in complete fractures. Cortical disruption and reverberating echo were present in all patients with complete and greenstick fractures. In conclusion, whether the fracture is complete or incomplete, subperiosteal hematoma, together with a cortical disruption, bending sign, or reverberating echo shown on US can confirm the fracture diagnosis in children.